Dinoflagelados (Dinophyta) de los órdenes Prorocentrales y Dinophysiales del Sistema Arrecifal Veracruzano, México - Parra-Toriz, Dulce (Universidad de Costa Rica, 2011)
inoflagellates are a major taxonomic group in marine phytoplankton communities in terms of diversity and biomass. Some species are also important because they form blooms and/or produce toxins that may cause diverse problems. The composition of planktonic dinoflagellates of the orders Prorocentrales and Dinophysiales, in the Veracruz Reef System, were obtained during the period of October 2006 to January 2007. For this, samples were taken from the surface at 10 stations with net of 30µm mesh, and were analyzed by light and scanning electron microscopy. Each species was described and illustrated, measured and their distribution and ecological data is also given. A total of nine species were found and identified, belonging to four genera: Dinophysis was represented by three species; Prorocentrum by three, Phalacroma by two, and only one species of Ornithocercus was detected. From the samples, four potentially toxin-producer species were found: Dinophysis caudata, D. rapa, Phalacroma rotundata and Prorocentrum micans. The number of species found in this study is low, especially considering the higher numbers observed in other areas of the Gulf of Mexico, where some reports have recorded up to 53 species of the order Dinophysiales and 14 for Prorocentrales. Identification keys for orders, genera and species for the study area are provided with this study. Rev. Biol. Trop. 59 (1): 501- 514. Epub 2011 March 01.